2013
DOI: 10.5433/1679-0359.2013v34n2p863
|View full text |Cite
|
Sign up to set email alerts
|

Componentes externos e gordura interna de novilhos Charolês ou Nelore alimentados com diferentes proporções de concentrado

Abstract: ResumoAvaliaram-se os componentes externos e a distribuição da gordura interna de novilhos das raças Charolês (CH) ou Nelore (NE), alimentados com diferentes proporções de concentrado na dieta. Os novilhos foram distribuídos em seis tratamentos que corresponderam a três níveis de concentrado: 35, 50 e 65% (com base na matéria seca) e dois grupos genéticos (Charolês e Nelore). Os novilhos NE alimentados com 65% de concentrado na dieta apresentaram maior rendimento de corpo vazio (RCV), não diferindo dos novilho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…This higher accumulation of inguinal and ruminal fats in the GC diet was possibly because of the diet's higher energy content (Table 1). The results of the present study are consistent with the reports of Silveira et al (2013), who found a higher total visceral fat weight in steers fed with 50% and 65% of concentrate in the diet, and of Missio et al (2009), who observed that animals fed with 79% of concentrate in the diet had a higher proportion of internal fat than those fed with 22% of concentrate. Missio et al (2009) observed that the deposition of rumen fat increased as the proportion of concentrate in the diet was increased.…”
Section: Thesupporting
confidence: 93%
“…This higher accumulation of inguinal and ruminal fats in the GC diet was possibly because of the diet's higher energy content (Table 1). The results of the present study are consistent with the reports of Silveira et al (2013), who found a higher total visceral fat weight in steers fed with 50% and 65% of concentrate in the diet, and of Missio et al (2009), who observed that animals fed with 79% of concentrate in the diet had a higher proportion of internal fat than those fed with 22% of concentrate. Missio et al (2009) observed that the deposition of rumen fat increased as the proportion of concentrate in the diet was increased.…”
Section: Thesupporting
confidence: 93%
“…Ferreira et al (2000) reported an increasing linear effect of concentrate content on internal fat weight in F1 Simmental x Nellore bulls. When evaluating the internal fat deposition in Charolais steers fed diets containing 35, 50 and 65% concentrate, Silveira et al (2013) observed higher internal fat weights in steers that received 50 and 65% of concentrate. In both studies, the increase in internal fat deposition was related to the increase in energy intake from the concentrate.…”
Section: Resultsmentioning
confidence: 92%
“…The content of concentrate in the ration also affects the weight of the internal organs (FERREIRA et al, 2000;MISSIO et al, 2009). The weight of these components at the time of slaughter exerts a strong influence on carcass yield, since heavier viscera increase the revenue of the abattoirs that sell these components to the animal feed industries, while the price paid to the producer for the carcass is lower (SILVEIRA et al, 2013).…”
Section: Introductionmentioning
confidence: 99%